2018
DOI: 10.1016/j.omto.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Effective Therapy Using a Liposomal siRNA that Targets the Tumor Vasculature in a Model Murine Breast Cancer with Lung Metastasis

Abstract: Although metastatic cancer is a major cause of death for cancer patients, no efficacious treatment for metastasis is available. We previously showed that the growth of a primary tumor could be inhibited by the administration of an anti-angiogenic small interfering RNA (siRNA) that is encapsulated in an RGD peptide-modified lipid nanoparticle (RGD-LNP). We herein report on the delivery of siRNA by an RGD-LNP to the vasculature is also effective for treating metastatic tumors. We compared the RGD-LNP with the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…[73][74][75][76][77] The inhibition of DLL4 by RGD peptide-modified lipid nanoparticles (RGD-LNPs) encapsulating siRNA prolongs the OS of mouse models of BC with lung metastasis. 78 In addition, lung metastasis in BC can be inhibited by the anti-cancer therapeutic peptides AD-01 and ALM201, which downregulate DLL4 and Notch4. 74 Preventing DLL4 activation in BC using antibodybased drugs represents another potential DLL4-targeting strategy, exhibiting potent anti-tumor activity in preclinical studies.…”
Section: Delta-like Ligands In Breast Cancermentioning
confidence: 99%
“…[73][74][75][76][77] The inhibition of DLL4 by RGD peptide-modified lipid nanoparticles (RGD-LNPs) encapsulating siRNA prolongs the OS of mouse models of BC with lung metastasis. 78 In addition, lung metastasis in BC can be inhibited by the anti-cancer therapeutic peptides AD-01 and ALM201, which downregulate DLL4 and Notch4. 74 Preventing DLL4 activation in BC using antibodybased drugs represents another potential DLL4-targeting strategy, exhibiting potent anti-tumor activity in preclinical studies.…”
Section: Delta-like Ligands In Breast Cancermentioning
confidence: 99%
“…[ 139 ] Due to the strong uptake in lung tissue, further work assessed the treatment of murine breast cancer metastases in the lungs using RGD‐YSK05 nanoparticles. [ 140 ] Delivery of siVEGFR2 resulted in significantly reduced VEGFR2 expression in cancerous regions of the lung but not in normal lung tissue, demonstrating the improved targeting ability of the nanoparticles (Figure 14E,F). [ 140 ] Similarly, delivery of siRNA against delta‐like ligand 4 (DLL4), another endothelial gene involved in neovascularization, showed improved overall survival in mice with lung metastases (Figure 14G).…”
Section: Preclinical Assessment Of Environment‐responsive Lipid/sirnamentioning
confidence: 99%
“…[ 140 ] Delivery of siVEGFR2 resulted in significantly reduced VEGFR2 expression in cancerous regions of the lung but not in normal lung tissue, demonstrating the improved targeting ability of the nanoparticles (Figure 14E,F). [ 140 ] Similarly, delivery of siRNA against delta‐like ligand 4 (DLL4), another endothelial gene involved in neovascularization, showed improved overall survival in mice with lung metastases (Figure 14G). [ 140 ] These studies suggest the potential for improved tumor‐specific targeting and efficient delivery of siRNA to enhance therapeutic effect.…”
Section: Preclinical Assessment Of Environment‐responsive Lipid/sirnamentioning
confidence: 99%
“…We also revealed that the RGD-MEND accumulated in TECs in tumor-bearing mice, and that an RGD-MEND encapsulating anti-VEGFR2 siRNA significantly inhibited tumor growth (50% effective dose: 0.75 mg/kg). The RGD-MEND could also be applied to a lung metastasis model [33]. In the case of a lung-metastasis model, VEGFR2 inhibition by the RGD-MEND failed to inhibit tumor growth.…”
Section: For Targeting Tumor Endothelial Cellsmentioning
confidence: 99%